Lymphocyte Signal Transduction - Tsoukas, Constantine.; Tsoukas, Constantine. (Springer US : Imprint: Springer, 2006)
Signal transduction through leukocyte receptors involves a variety of signaling molecules including kinases, phosphatases, adaptor proteins, small GTPases GTP exchange factors, membrane phospholipids as well as others. These signal transducers, regulated by inter- and intra-molecular interactions, as well as by various post-translational modifications, lead to the activation of transcription factors that mediate cellular differentiation and growth, effector cell functions, and apoptotic cell death. Several investigators from various parts of the world convened at the 3rd Lymphocyte Signal Transduction Workshop in Crete, Greece from May 27 to June 1, 2005 to discuss their most recent findings in leukocyte signaling. This volume represents a collection of topics discussed during the conference.